Efficient modelling of forces and local strain evolution during delamination of composite laminates. (April 2015) - Airoldi, Alessandro; Baldi, Andrea; Bettini, Paolo; Sala, Giuseppe
Abstract: FEM analyses based on cohesive zone models are a well-assessed methodology to predict onset and propagation of delamination in composites. In this work, a specific modelling technique based on a cohesive zone model is applied to analyse Double Cantilever Beam (DCB) and 4-point bending End Notched Flexure (4-ENF) tests, focusing on the evolution of forces as well as of internal local strains, which have been monitored by Fibre Bragg Grating sensors embedded in the specimens. The numerical approach is based on explicit FEM computations and presents some appealing advantages with respect to conventional models, since it does not use zero-thickness cohesive elements and does not require a non-physical penalty stiffness to be introduced between adjacent plies. In the cases presented, such approach is applied to model both force response and local strain evolution during the stable propagation of delamination in mode I and mode II, in the presence of fibre bridging phenomena and taking into account frictional effects between crack faces. The paper presents the experimental results and analyses the data acquired by the sensors embedded in the specimens. Then, the general accuracy and the computational advantages of the numerical approach proposed are evaluated considering numerical benchmarks. Models of the tests are developed at different levels of through-the-thickness mesh refinement and sensitivity analyses are performed to point out the effects on the overall and local response of significant model parameters, such as the length attributed to the process zone in the cohesive zone model and the friction coefficient in the contact interaction between crack faces. Numerical results and numerical–experimental correlation prove that the modelling technique and the methodologies applied to represent fibre bridging and frictional effects represent efficient tools to reliably model complex delamination processes .